Transient non-confining potentials for speeding up a single ion heat pump. (10th October 2018) - Torrontegui, E; Dawkins, S T; Göb, M; Singer, K
Abstract: We propose speeding up a single ion heat pump based on a tapered ion trap. If a trapped ion is excited in an oscillatory motion axially the radial degrees of freedom are cyclically expanded and compressed such that heat can be pumped between two reservoirs coupled to the ion at the turning points of oscillation. Through the use of invariant-based inverse engineering we can speed up the process without sacrificing the efficiency of each heat pump cycle. This additional control can be supplied with additional control electrodes or it can be encoded into the geometry of the radial trapping electrodes. We present a novel insight into how speed up can be achieved through the use of inverted harmonic potentials and verify the stability of such trapping conditions.